1984
DOI: 10.1007/bf01412036
|View full text |Cite
|
Sign up to set email alerts
|

High resolution electron microscopy of (SN)x

Abstract: Abstract:Pristine and iodinated (SN) x were studied by high resolution electron microscopy. High resolution electron micrographs showing lattice fringes up to 0.22 nm were obtained. In these electron micrographs, the texture of (SN) x crystals was elucidated to be fibrillar or mosaic; the lattice fringes were observed in domains extended along the molecular axis (b-axis) and very narrow in the perpendicular direction. Each crystallite varied from place to place in size but maintained the b-axis orientation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 19 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…[33] Highresolution electron microscopy shows the microfibrillar morphology of (SN) x and also that crystals are composed of a large number of small, microtwinned crystallites. [34,35] A scanning tunneling microscopy image also revealed the surface microtwin (100) structure with a series of ridges along the chain axis. This twinning occurs less frequently in crystals grown using the Nakada method (Sec.…”
Section: Crystal Structurementioning
confidence: 98%
“…[33] Highresolution electron microscopy shows the microfibrillar morphology of (SN) x and also that crystals are composed of a large number of small, microtwinned crystallites. [34,35] A scanning tunneling microscopy image also revealed the surface microtwin (100) structure with a series of ridges along the chain axis. This twinning occurs less frequently in crystals grown using the Nakada method (Sec.…”
Section: Crystal Structurementioning
confidence: 98%
“…This means that the iodine atoms diffuse along the direction of the molecular chain at the largest rate. Moreover, the observation of lattice fringes by high resolution electron microscopy revealed that the size of fibrils is not uniform but varies widely from a single chain to a large single-crystal-like domain [14]. The (SN)x crystals comprise fine and long fibrils which are a few tens nm in lateral dimension and extended extremely in the direction of chain axis [5,13].…”
Section: I' (V) = K Z • A(i) B~) 6 (Vt/-ffi L/-~i)mentioning
confidence: 99%
“…The (SN)x crystal has a fiber structure consisting of fine fibrils [2,13,14] and the electron diffraction pattern of (SN)x doped with halogen shows a characteristic feature [5,6]. From close examination of the Xray and electron diffraction patterns, it was found that the halogen atoms are localized in the disordered regions of the (SN)x matrix crystal and their localization is closely related to the fibrillar nature of crystals.…”
Section: Introductionmentioning
confidence: 99%